Improvements in the environmental aspects and impacts matrix for the agricultural machinery sector - Ponte, Paulo Renato Maceira Merola; Fernandes, Nilson José; Araújo, Fernando de; Cardoso, Lucas de Souza (Brazilian Journal of Production Engineering, 2026)
The article addresses the application of the Environmental Aspects and Impacts Matrix in the management of environmental risks in an agricultural machinery industry. The main objective of the study is to support the maintenance of ISO 14001 certification and to reduce the environmental impacts of production activities. The research adopts a quantitative and exploratory approach, using process analysis to identify and quantify environmental impacts. To this end, an improvement proposal for the Matrix was implemented, structured into four stages: identification, characterization, significance assessment, and definition of control actions. As part of continuous improvement, an interactive system was developed in Microsoft Power BI® to facilitate the visualization and management of environmental risks. The results indicate a 49.4% reduction in significant environmental impacts, a 69.5% increase in the number of environmental projects implemented, and a 269.5% increase in the reduction of non-value-added (NVA) activities, reflecting greater production efficiency. Additionally, operational costs were reduced by 389.8% compared with the previous period. In the qualitative dimension, greater employee engagement in adopting sustainable practices was observed, strengthening the organizational culture focused on sustainability.
Keywords: Environment; ISO 14001; environmental aspects and impacts